Kajian Mitigasi pada Zona Rawan Tanah Longsor Berdasarkan Tipe Longsoran di Kecamatan Kokalukuna dan Kecamatan Bungi, Kota Baubau Provinsi Sulawesi Tenggara: Mitigation Study on Landslide Prone Zone Based on Landslide Type in Kokalukuna District and Bungi District, Baubau City, Southeast Sulawesi Province - Indriati, Sri; Sultan, Sultan; Azikin, Busthan (Jurnal Ecosolum, 2023)
The tropical climate condition of Baubau City which is located at 5°21'- 5°30' South Latitude 122°30' - 122°45' East Longitude causes the Kota Baubau Region which describes the tropics to experience more intensive weathering. Most of the landslides that occurred in Baubau City were in areas with unstable geological conditions and were often triggered by heavy rains that exceeded the highest point. This study aims to determine the causes of landslides, types of landslides, and countermeasures. In this study, measurements of slope geometry were carried out which included slope height and slope angle, testing rock and soil samples at the research station, as well as observing other supporting factors. The results of the study show that 3 stations have avalanche-prone zones. The causes of landslides are slopes with a slope angle of > 400 at station 1 of 530, station 2 of 410 and station 3 of 610, rainfall in the study area reaches the highest point of 714 MM, human activities such as dredging under the slope and construction of shaft roads cause slope instability and cause hazards such as landslides and vibrations. The types of avalanches at stations 1 and 2 are avalanches, while at station 3 the slides and falls are viewed from the geometry of the slopes processed by Autocad, the appearance of the research station and the results of the geostudio simulation show the shape of the slip plane with a FoS value of <1.07. Based on the results of research at 3 research station points, there is a potential for landslides to occur. The countermeasures methods used are structural mitigation, building of cliff reinforcement walls, surface soil stripping and increasing slope stability, namely changing the slope geometry. Non-structural mitigation, namely by providing information to the BPBD and the community regarding landslides.